2019
DOI: 10.1039/c9ta08679j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of tin-based perovskite solar cells induced by an ammonium hypophosphite additive

Abstract: Bi-functional ammonium hypophosphite (AHP) is introduced to improve the performance and long term stability of FASnI3 solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 50 publications
0
108
0
Order By: Relevance
“…It can be found that the solar cells with WS 2 interlayer has a lower leakage current than that of the control one, indicating the decreased carrier generation rate and background carrier density in the device. Because the carrier generation rate in a solar cell is related to the trap density in the device, [ 40–42 ] this result indicates that the introduction of WS 2 can decrease the trap density in the devices.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the solar cells with WS 2 interlayer has a lower leakage current than that of the control one, indicating the decreased carrier generation rate and background carrier density in the device. Because the carrier generation rate in a solar cell is related to the trap density in the device, [ 40–42 ] this result indicates that the introduction of WS 2 can decrease the trap density in the devices.…”
Section: Resultsmentioning
confidence: 99%
“…The 2D/3D perovskite layer showed improved morphology and band-level alignment compared with 3D FASnI3 layer. As a result, the 2D/3D champion PSCs achieved a PCE of 7.86 % with a Jsc of 22.6 mA/cm 2 , a Voc of 0.54 V, and an FF of 64% [76]. Kayesh et al studied the effects of doping 5-ammonium valeric acid iodide (5-AVAI) in 3D FASnI3 film; they found 5-AVAI can passivate the grain boundaries, suppress the Sn 2+ oxidation, and enhance the charge carrier lifetime.…”
Section: D/3d Sn Perovskite Solar Cellsmentioning
confidence: 96%
“…Moreover, the devices exhibited good long-term stability both in pure N 2 and ambient atmospheres [74]. Today, high-performance Sn-based PSCs are mainly based on FASnI 3 as light absorber [75][76][77][78]. Table 2 shows some key photovoltaic parameters of FASnI 3 .…”
Section: Fasni3mentioning
confidence: 99%
“…The reducing process was proposed to be Sn4++3H2PO2-Sn2++2HPO32-+PH4+ , during which the oxidized Sn 4+ was converted back to Sn 2+ and led to reduced defects (Figure e). Moreover, AHP was found to be able to effectively suppress the phase separation of SnCl 2 and assist the growth of perovskite grain (Figure f) …”
Section: Reducing Agents For Performance Enhancementmentioning
confidence: 99%
“…(f) SEM images of FASnI 3 films processed with 0%, 3%, 5% and 7% AHP. (d–f) Reproduced with permission . Copyright 2019, The Royal Society of Chemistry.…”
Section: Reducing Agents For Performance Enhancementmentioning
confidence: 99%